2021
DOI: 10.35137/jabk.v8i1.486
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Sosialisasi Perpajakan terhadap Niat untuk Mematuhi Kewajiban Perpajakan Calon Wajib Pajak dengan Kesadaran Pajak sebagai Variabel Intervening

Abstract: This study aims to reveal whether the socialization of taxation to high school students in Yogyakarta has an effect on their intention to comply with taxes through tax awareness. This research data uses direct / primary data. The sampling method is convenience sampling. The data analysis technique is path analysis with the socialization of taxation being the independent variable and the intention to comply with taxes as the dependent variable, and tax awareness being the intervening variable. The results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…and Sari & Saryadi (2019) shows that tax knowledge has a significant influence on taxpayer compliance, Different findings were found by Jackfruit et al ( 2014) and…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…and Sari & Saryadi (2019) shows that tax knowledge has a significant influence on taxpayer compliance, Different findings were found by Jackfruit et al ( 2014) and…”
Section: Methodsmentioning
confidence: 75%
“…Based on this background, the researcher formulated the first hypothesis, namely: H1: Quality of service has a significant effect on taxpayer compliance Utomi (2011) explaines that taxpayer knowledge is the capability that taxpayers have in understand any regulatory taxation, whether it's about the statutory tax rates they'll pay or the tax benefits that will be handy to them. Marfila (2019) and Sari & Saryadi (2019) found that taxpayer knowledge has a significant effect on taxpayer compliance. Based on this background, the researcher formulated the second hypothesis, namely:…”
Section: Hypothesismentioning
confidence: 99%
“…Sosialisasi pajak menjadi suatu perihal penting dalam kaitannya dengan menumbuhkan niat patuh pajak serta memberikan informasi seputar pajak (Wardani et al, 2021). Melalui sosialisasi pajak, informasi yang diperoleh wajib pajak maupun calon wajib pajak secara perlahan dapat mengubah pola pikir mereka terhadap pajak sehingga mendorong mereka agar bisa patuh terhadap pajak.…”
Section: Pendahuluanunclassified
“…Melalui informasi tersebut, wajib pajak akan paham tentang perpajakan sehingga dapat menumbuhkan niat wajib pajak untuk memenuhi kewajiban perpajakannya. Berdasarkan penelitian dari Wardani et al (2021), sosialisasi perpajakan berpengaruh positif terhadap niat patuh pajak.…”
Section: Pendahuluanunclassified
“…Konsekuensinya, sosialisasi perpajakan berdampak baik terhadap kepatuhan pajak (Burhan, 2015). Hasil yang sama juga menunjukkan bahwa sosialisasi pajak memiliki dampak yang efektif terhadap kepatuhan pajak (Wardani et al, 2021). Namun, ada hasil penelitian yang menunjukkan bahwa sosialisasi pajak memiliki efek yang buruk terhadap kepatuhan pajak (Winerungan, 2013).…”
Section: Pendahuluanunclassified